Respuestas
Respuesta dada por:
3
El cuadrado de la diferencia de 29 y 23
![(29-23) ^{2} = 6^{2} = 36 (29-23) ^{2} = 6^{2} = 36](https://tex.z-dn.net/?f=%2829-23%29+%5E%7B2%7D++%3D++6%5E%7B2%7D+%3D+36+)
El cuadrado de la suma de 2 y 4
![(2+4) ^{2} = 6^{2} = 36 (2+4) ^{2} = 6^{2} = 36](https://tex.z-dn.net/?f=%282%2B4%29+%5E%7B2%7D++%3D++6%5E%7B2%7D++%3D+36)
ahora dividimos:
![\frac{36}{36} = 1 \frac{36}{36} = 1](https://tex.z-dn.net/?f=+%5Cfrac%7B36%7D%7B36%7D+%3D+1)
El cuadrado de la suma de 2 y 4
ahora dividimos:
Preguntas similares
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 10 años
hace 10 años